Thermal free-surface immersed-boundary lattice Boltzmann method for free surface flows with a liquid-solid phase transition - Badarch, Ayurzana; Hosoyamada, Tokuzo (Journal of Applied Science and Engineering A, 2022)
This paper reports on the progress of the liquid-solid phase transition modeling of water in open channel flow by using the lattice Boltzmann method with the immersed boundary modification. The phase transition in a fluid flow has a moving interface between the liquid and solid state, which leads complicated treatments in existing numerical models. By applying the immersed boundary modification in the lattice Boltzmann method and the non-iterative enthalpy approach for the separation of the states, the moving boundary of the melting or solidification front is solved without any difficulty. The ice bed and the submerged ice cover under dynamic flow conditions is exercised to demonstrate the model performance. The model is extremely suitable in the formulation in terms of its simple and compact framework extendable to any dimensions.